A class of distal functions on semitopological semigroups
The norm closure of the algebra generated by the set {nλ^n^k: λT and kN } of functions on (Z , +) was studied in S (and was named as the Weyl algebra). In this paper, by a fruitful result of Namioka, this algebra is generalized for a general semitopological semigroup and, among other things, it is shown that the elements of the involved algebra are distal. In particular, we examine this algebra for (Z , +) and (more generally) for the discrete (additive) group of any countable ring. Finally, our results are treated for a bicyclic semigroup., number=2, journal=Methods of Functional Analysis and Topology, author=Vishki, H. R. and Jabbari, A., year=2009, month=Jun., pages=188–194